1986
DOI: 10.1159/000469344
|View full text |Cite
|
Sign up to set email alerts
|

Changes in NADH-Ubiquinone Reductase (Complex I) with Autolysis in the Rat Heart as Experimental Model

Abstract: Complex I (NADH-ubiquinone reductase) is a complex system located in the inner mitochondrial membrane and has the ability to catalyse several different enzymatic reactions concerned in electron transport. It is known to be one of the first components of the respiratory chain to be damaged by ischemia. Our results, using autolysis in the rat heart as experimental model, indicate that the NADH dehydrogenase system was impaired relatively early during ischemia while transhydrogenation and NADPH dehydrogenation ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

1988
1988
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
1
3
1
Order By: Relevance
“…The mean plasma coenzyme Q10 level of patients included in the study who had significant CAD with no systolic dysfunction were similar to that of healthy individuals, reported in the literature. These results are not consistent with the prior studies conducted in CAD patients (13,14).…”
Section: Discussioncontrasting
confidence: 99%
“…The mean plasma coenzyme Q10 level of patients included in the study who had significant CAD with no systolic dysfunction were similar to that of healthy individuals, reported in the literature. These results are not consistent with the prior studies conducted in CAD patients (13,14).…”
Section: Discussioncontrasting
confidence: 99%
“…NADH-ubiquinone reductase catalyzes the reaction from NADH to NADþ during the process of electron transport [27]. We also found that DiOC5(3) significantly increased the NADH/NADþ ratio in isolated mitochondria (P < 0.05; Fig.…”
Section: Dioc5(3) Induced Apoptosis With Ros Overproduction In Aldhþ supporting
confidence: 56%
“…This correlation was associated with severity of disease, but they did not observe statistically significant relationship between the MPV level and mortality (8 (13). They also reported that elevated MPV was an independent predictor of inhospital mortality in ADHF patients (13). Thus, HFrelated hospitalization was markedly higher in MPV > 8.4 fL group than MPV ≤ 8.4 fL group (73.0% vs. 12.2%, p<0.001), although mortality difference was not statistically significant between the two groups in our study (p=0.457).…”
Section: Discussionmentioning
confidence: 93%
“…They also demonstrated a correlation between the elevated MPV level and worse right heart haemodynamics in PAH patients (8). This correlation was associated with severity of disease, but they did not observe statistically significant relationship between the MPV level and mortality (8 (13). They also reported that elevated MPV was an independent predictor of inhospital mortality in ADHF patients (13).…”
Section: Discussionmentioning
confidence: 97%